INVENTÁRIO E AVALIAÇÃO DAS ÁREAS PROTEGIDAS NA REGIÃO CENTRO E NORDESTE DE MATO GROSSO DO SUL - PIMENTA, Jéssica Maia Alves1; SOARES, Afrânio José Soriano; MOIMAZ, Minéia; BATISTA, Raphael Luís Matheus (ANAIS DO ENIC, 2017)
-